New Group Counseling Competencies Scale-Short Form to Supervise Group Counselor Candidates - Taufiq, Agus; Herdi, Herdi (Jurnal Kajian Bimbingan dan Konseling, 2020)
Assessment of Group Counseling Competencies Scale (AGCCS) is one of the questionnaires important to assess group counseling competencies. The objective of this study is to adopt and test the psychometric properties of New Group Counseling Competencies Scale-Short Form (NGCCS-SF). This study used a new instrument adaptation procedure. A total of 73 candidates of group counselors from twoStudy Program of Guidance and Counseling in Indonesia were the participants of this study. The data of group counseling competencies were measured using NGCCS-SF. Operationally, data analysis used Rasch Model 3.75. The results of the study show that NGCCS-SF has satisfying psychometric properties. NGCCS-SF can be used as an effective and valid assessment tool for group counselor candidates in counselor education and supervision in Indonesia.